Google Classroom as The Teaching Media Based on The Concept of Tat Twam Asi - Dewa Gede Bambang Erawan; I Gusti Ayu Putu Tuti Indrawati; A. A. Istri Yudhi Pramawati; Ratna Dwi Anjani Putri (International Journal of Elementary Education, 2022)
The current pandemic has caused a change in the learning system in Indonesia to be centered on online learning. Students, teachers, and parents are forced to be able to carry out online learning. Learning media can generate critical thinking processes and learning creativity, considering the many gaps in the learning process. Google Classroom learning media based on the concept of "Tat Twam Asi" is a solution to the learning process. This research aims to develop Google Classroom learning media based on the "Tat Twam Asi" concept to help implement learning during a pandemic. This type of research is developed using the ADDIE model. Media experts conducted design trials (expert validation). Group trials were conducted on teachers and students. The methods used to collect data are observation, interviews, and questionnaires. The instrument used in collecting data is a questionnaire. Qualitative data analysis was used in this study. The research results are the validation results of media experts at 4.58 with the appropriate/very good category. Trials conducted on groups of teachers show that Google Classroom learning media is decent/good (4.3). Tests on groups of students show that Google Classroom media is in the proper/very good category (4.51). It was concluded that Google Classroom learning media is suitable for learning.